SOEKARNO AND SUN YAT SEN STRUGGLING FOR LIBERTY AND NATIONALISM - Isbodroini Suyanto (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractIr Soekarno, born on June 1st 1091, and Dr. Sun Yat-sen, born in 1866, were unforgottenleaders until present. Soekarno was a leader determined to struggle for Indonesia’s libertysince the colonial period. He felt how the people suffered those days because of theexploitation of the colonialist. His dream was to form an independent country based onnationalism. He realized that Indonesia, at that time the Dutch Indies, was plural, so hebelieved that nationalism based on humanity was the most appropriate, although he wasstrongly challenged by Islamic groups who wanted a country with Islamic principle. Afterindependence, Pancasila became Indonesian state philosophy.Soekarno’s struggle during the colonial period was influenced by several leaders who werealso struggling for freedom from exploitation, both by colonialism or the power of absolutemonarchy. Several of them, such as Mahatma Gandhi, Aurobindo Ghose and Sut Yat Sen,struggled against Manchu monarchy. Sun Yat Sen’s principle about nationalism, whichwas based on The Three Principles of the People (Sanminxhuyi) apparently influencedSoekarno in struggling for nationalism. Sun Yat Sen’s struggle became reality with thebirth of China Revolution in 1911Keywords: Nationalism, Struggle for independence, Freedom, Justice